Detection of Î²-lactamases producing Methicillin-Resistant Staphylococcus aureus (MRSA) - K. Al-Kudheiri, Mee’aad; N. Hussein, Azhar; M. Al-Mohana, Ali (Al-Qadisiyah Journal of Pure Science, 2018)
Methicillin resistant Staphylococcus aureus (MRSA) is one of the most important causes of nosocomial and community infections and most clinical isolates are Î²-lactams and multidrug resistant. Resistance to Î²-lactam antibiotics is most often due to penicillin binding proteins (PBPs) and Î²-lactamases production. Characterization of Î²-lactamases is important for choosing appropriate antibiotic therapy, therefore 135 S. aureus were collected from 343 clinical samples between August 2012 and January 2013 from several clinical sources that were randomly selected from patients in three main hospitals in Al-Najaf city and the prevalence of MRSA in Najaf hospitals was 64 (47.4%) and the remaining 71 (52.6%) isolates were MSSA, and all MRSA isolates were tested for Î²-lactamase production by using seven methods: [cloverleaf test, Masuda double-disc test, iodometric method, acidometric method, chromogenic (nitrocefine) method, double disc method and penicillin disc diffusion method]. The findings of this study revealed that chromogenic (nitrocefine) method, cloverleaf test and Masuda test had a high accuracy (100%) comparative with other methods tested for detection of MRSA Î²-lactamase production.